Body temperature variation of South African antelopes in two climatically contrasting environments - Shrestha, A.K.; van Wieren, S.E.; van Langevelde, F.; Fuller, A.; Hetem, R.S.; Meyer, L.C.R.; de Bie, S.; Prins, H.H.T. (Journal of thermal biology, 2012)
To understand the adaptive capacity of a species in response to rapid habitat destruction and climate change, we investigated variation in body temperature (Tb) of three species of antelope, namely eland, blue wildebeest and impala, using abdominally-implanted temperature data loggers. The study was conducted at two climatically contrasting environments in South Africa, one with a less seasonal and mild winter (Mapungubwe National Park) and the other with a more seasonal, long and cold winter (Asante Sana Game Reserve). Since the habitat with long and cold winters would be suboptimal for these African antelopes, which evolved in less seasonal and hot environments, antelopes in Asante Sana were expected to exhibit a larger amplitude in Tb and a lower minimum body temperature (MinTb) during winter to reduce Tb and the ambient temperature (Tb−Ta) gradient to save energy. In both eland and impala, 24-h body temperature amplitude did not differ between the study sites, regardless of season. Conversely, wildebeest in Mapungubwe showed a higher variability in the 24-h amplitude of body temperature and also a lower MinTb during winter and spring than the wildebeest in Asante Sana. This variation in Tb among Mapungubwe wildebeest was influenced by both the amplitude of ambient temperature (positive) and cumulative rainfall (negative), which was not the case for wildebeest in Asante Sana. We propose that the low MinTb of wildebeest in Mapungubwe was the result of nutritional stress during winter and spring; an evident response even during a year of average rainfall. Therefore, these wildebeest apparently live in a physiologically stressful environment. With the predicted increase in the frequency and intensity of drought periods in southern Africa, wildebeest and other grazers, will likely experience greater nutritional stress in the future.